The Importance of Stakeholder Ownership for Capacity Development Results - Smithers, Nicola (World Bank, Washington, DC, 2015)
Capacity development is widely accepted as critical to achieving the Millennium Development Goals (MDG) and other development outcomes, but the results from capacity development initiatives have often been disappointing. This challenge signifies the urgent need to advance capacity development knowledge and practice. As a contribution to addressing this challenge, the World Bank Institute (WBI) has developed a strategic, country-led and approach to results focused capacity development, which involves collective action across society and an emphasis throughout on achieving results. The conceptual framework and processes for WBI’s approach are captured in the Capacity Development and Results Framework (CDRF) (Otoo, Agapitova and Behrens 2009). The focus of this paper is on the strength of stakeholder ownership. Drawing on a review of recent studies, literature and relevant examples, this paper seeks to deepen understanding of the importance of stakeholder ownership and its contributing institutional characteristics to achieving development goals. The paper identifies future collaborative research that would shed light on which change strategies are likely to be most effective in strengthening stakeholder ownership in different contexts.